2020
DOI: 10.3126/jcmc.v10i2.29664
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and microbiological analysis of bottled water in Pokhara, Nepal

Abstract: Background: Today possibility of rendering water non-potable by various types of contaminants (physical, chemical and biological) is of considerable importance. It is not only the microbial con­taminants but also the physical and chemical contaminants, playing an important role in compro­mising our health in many ways. The aim of this study was to assess the physical, chemical and the microbiological quality of commercially produced bottled water in Pokhara city. Methods: A study was conducted to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…As excessive TD protects pathogenic microorganisms from disinfectants, it poses a health risk to people who consume it (Tiwari & Singh, 2014). Our results were similar to those of bottled drinking water from Pokhara (Maskey et al, 2020) and from the Chimdi Lake in the Sunsari District of Nepal (Das, 2017). It has been found that the 51.5% of samples (Sudarshana et al, 2019), 36% of samples from groundwater (Koju et al, 2014), and bottled drinking water (Burlakoti et al, 2020) in Kathmandu, as well as spring drinking water of central development region of Nepal (Pandey & Shakya, 2011), have exceeded the WHO guidelines.…”
Section: Tdsupporting
confidence: 80%
See 1 more Smart Citation
“…As excessive TD protects pathogenic microorganisms from disinfectants, it poses a health risk to people who consume it (Tiwari & Singh, 2014). Our results were similar to those of bottled drinking water from Pokhara (Maskey et al, 2020) and from the Chimdi Lake in the Sunsari District of Nepal (Das, 2017). It has been found that the 51.5% of samples (Sudarshana et al, 2019), 36% of samples from groundwater (Koju et al, 2014), and bottled drinking water (Burlakoti et al, 2020) in Kathmandu, as well as spring drinking water of central development region of Nepal (Pandey & Shakya, 2011), have exceeded the WHO guidelines.…”
Section: Tdsupporting
confidence: 80%
“…All samples analyzed in this study were found to be within the NDWQS and WHO allowable limits. Other studies have shown that the EC values varied from 1.00 to 48 in bottled drinking water supplied to Pokhara (Maskey et al, 2020) and from 312.2 to 377.8 μS/cm in Chimdi Lake of Sunsari District, Nepal (Das, 2017). Furthermore, 2% of samples (Koju et al, 2014) and 16.5% of samples (Sudarshana et al, 2019) in Kathmandu Valley exceeded the NDWQS and WHO guidelines for EC.…”
Section: Ecmentioning
confidence: 89%
“…A turbidity meter is a instrument used to measure the turbidity of water or a solution. Turbidity is expressed in the concentration of insoluble or the level of clarity of the liquid expressed in Nephelometric Turbidity Units (NTU) [37]. Turbidity measurement is based on comparing the intensity of light scattered by the sample under the specified conditions with the intensity of light scattered by the reference standard suspension under the same conditions.…”
Section: B C D Ementioning
confidence: 99%
“…The pH is considered as a secondary contamination of drinking water. Water with low pH is acidic, naturally soft and corrosive in nature, while drinking water with pH above 8.5 indicates the presence of high levels of alkalinity minerals having aesthetic effect (Maskey et al, 2020).According to WHO (2004) guidelines, pH has no direct impact on human health, but is considered as one of the most important operational water quality parameters. The pH of tested samples ranged from 5.83 to 7.5.…”
Section: Physico-chemical Analysis (Table 1; Figures 1and 2)mentioning
confidence: 99%